Desarrollo experimental de condiciones de extracción de té verde comercial con altos contenidos de egcg para aplicación en salud humana (2024)
Green tea is obtained from the species Camellia sinensis, which has high contents of catechins, possessing antioxidant, anti-inflammatory, and anticancer properties. Among the most studied is epigallocatechin-gallate (EGCG) as it is found in greater proportion, considered the most potent bioactive compound in green tea, and due to its antimicrobial effects, it can contribute to oral health. Therefore, the objective of the project was to develop experimental extraction and drying conditions for premium green tea leaves to obtain high EGCG contents for application in a magistral formulation. To achieve this, a protocol for the extraction and drying of premium green tea was developed to contain high percentages of EGCG, which was established by standardizing an analytical method for its evaluation; and finally, the incorporation of lyophilized tea into a magistral formulation was evaluated, as well as its stability through a forced degradation study. Finally, the content of EGCG and caffeine was 1.58 mg/g and 82.31 mg/g in the green tea powder, respectively; in the forced degradation studies, no decrease in concentration over time or incorporation of the tea was observed, but after changes in sample preparation before entering the equipment for evaluation, a slight degradation of EGCG was observed. Therefore, the green tea extraction conditions were optimized, and simultaneously, issues in the preparation protocol of the magistral formulation were evidenced.